Safety of classic and biologic systemic therapies for the treatment of psoriasis in elderly: an observational study from national BIOBADADERM registry. (3rd September 2014) - Medina, C.; Carretero, G.; Ferrandiz, C.; Dauden, E.; Vanaclocha, F.; Gómez‐García, F.J.; Herrera‐Ceballos, E.; De la Cueva‐Dobao, P.; Belinchón, I.; Sánchez‐Carazo, J.L.; Alsina, M.; López‐Estebaranz, J.L.; et al.
Abstract: Background: Psoriasis patients over 65 years‐old (elderly) constitute a growing group, underrepresented in clinical trials, and likely to be more prone to adverse events. Objective: To describe safety of systemic psoriasis therapy in patients over 65 years‐old compared to younger patients. Methods: Patients registered in Biobadaderm, a Spanish national registry of psoriasis patients treated with systemic therapy, were grouped in elderly (≥ 65 years old) and younger patients. Rates of adverse events were described by severity and type, and the risks compared in both groups, taking into account exposure to classic or biologic drugs, using Cox regression. Results: 175 (9.8%) of 1793 patients were elderly. Overall risk of adverse events was not higher in elderly (drug group adjusted HR 1.09 (95%CI: 0.93‐1.3)). Serious adverse events were more common in elderly (drug group adjusted HR 3.2 (95%CI: 2.0‐5.1)). Age adjusted HR of all adverse events was lower for patients exposed to biologics compared to classic drugs in the whole sample (HR 0.7 (95%CI: 0.6‐0.7)). Age did not seem to modify the effect of therapy (biologic vs. classic) in the risk of adverse events (likelihood ratio test for interaction, p = 0.12 for all adverse events, p = 0‐09 for serious adverse events). Conclusions: Serious adverse events are more common in elderly patients, although they may be related to other variants that are associated with this age group and not due to the treatment itself. Use of biologics was associated with lower risk of adverse events in the whole group. We found no differences in this association between young and elderly. These results are reassuring, although uncontrolled confounding could not be excluded as an explanation for these findings, and the power of the study to detect differences was low.